SAT0252 The number of treg cells in peripheral blood in pss patients is decreased and low dose IL-2 can promote its proliferation. (15th June 2017) - Miao, M; Hao, Z; Guo, Y; Zhang, X; Zhang, S; Wu, X; Xu, D; Gao, C; Li, X
Abstract : Background: PSS is a kind of autoimmune disease without clear pathogenesis. Treg cell plays an important role in autoimmune disease. However, opinions about change of amount of Treg cells in peripheral blood in autoimmune disease are various. Besides, the researches mainly focus on RA and SLE but not PSS. Objectives: To explore the change of the number of Th17 and Treg (CD4+CD25+Foxp3+T cells) cells in peripheral blood in PSS and the effects of low dose IL-2 therapy on the balance of Treg and Th17 cells. Methods: One hundred and ninety two PSS patients in our department, and 30 healthy controls were put in the research. The amount of Th17 cells and Treg cells were calculated by flow cytometry. Eighty eight in 192 were given low-dose IL-2 (50 WIU/day for 5 days) by hypodermic injection combined with standard therapy which includes glucocorticoid, immune-suppressants, biological agents or combination of them, while others (12 in 69) were given standard therapy only. The amount of these cells were calculated again after therapy. Results: There was significant decrease in the absolute number of Treg cells and significant increase of the ratio of Th17/Treg cells in PSS patients when compared with healthy controls. There was no significant difference in absolute number of Th17 cells between PSS patients and healthy controls. Further, the number of Treg cells were negatively relative to ESSDAI. Traditional DMARDs had no obvious impact on Treg and Th17 cells. The amount of Treg cells significantly increased after the treatment of IL-2 by 1 week. But there was no significant improvement in clinical manifestations in the short time when comparing combinational treatment of IL-2 and classical drugs with classical therapy. No obvious adverse reactions were observed. Conclusions: The number of CD4+CD25+Foxp3+T cells in peripheral blood was decreased obviously and was inversely related to ESSDAI. While there was no significant difference of Th17 cells between PSS patients and healthy controls. And there was no correlation between the number of Th17 cells and ESSDAI. So the imbalance of Th17/Treg is due to the decrease of Treg cells not increase of Th17 cell which indicates that the pathogenesis of PSS maybe mainly because of shortage of autoimmune tolerance. Low dose IL-2 therapy can effectively promote proliferation of Treg cells by which low dose IL-2 may induce and restore autoimmune tolerance to benefit disease control. References: Takayoshi Morita et al. The Proportion of Regulatory T Cells in Patients with Rheumatoid Arthritis: A Meta-Analysis. PLoS One. 2016 Sep 13. Noack, M. & Miossec, P. Th17 and regulatory T cell balance in autoimmune and inflammatory diseases. Autoimmun Rev. 13, 668–677 (2014). Disclosure of Interest: None declared